Estrategias didácticas y su incidencia en el aprendizaje del mantenimiento de máquinas eléctricas a los estudiantes de electricidad en el Colegio Fiscal Bachillerato Simón Bolívar de la ciudad de Guayaquil, Provincia del Guayas - Hidalgo Terán, Juan Miguel (2019)
Learning electrical machine maintenance has been a topic of interest in the different research fields in high school education. Consequently, the problems that emerge are usually common, so the objective of developing a proposal with didactic strategies which allow tailoring the learning supported on the maintenance of electrical machines was raised. The research was carried out through the perspective of the qualitative and quantitative modality which implies the empirical research approach, it was necessary to make a tour and a theoretical analysis of different paradigms about teaching and learning strategies, applying a survey allowed us to measure such learning, the lack of didactic strategies of teachers impairs the students’ meaningful learning, which permitted the verification of the working hypothesis through the application of the hypothetical-deductive method. Therefore, an innovative alternative proposal is suggested, through methodological guidance with didactic strategies to encourage students’ motivation and self-learning